Cycle analytics for traders : advanced technical trading concepts - Ehlers, John F., 1933- (Hoboken, New Jersey : John Wiley and Sons, Inc., 2014)
"This is a technical resource book written for self-directed traders who want to understand the scientific underpinnings of the filters and indicators they use in their trading decisions. There is plenty of theory and years of research behind the unique solutions provided in this book, but the emphasis is on simplicity rather than mathematical purity. In particular, the solutions use a pragmatic approach to attain effective trading results. Cycle Analytics for Traders will allow traders to think of their indicators and trading strategies in the frequency domain as well as their motions in the time domain. This new viewpoint will enable them to select the most efficient filter lengths for the job at hand. This book will: Show an awareness of Spectral Dilation, and how to eliminate it or to use it to your advantage. Discuss how to use Automatic Gain Control (AGC) to normalize indicator amplitude swings. Explain thinking of prices in the frequency domain as well as in the time domain. Create an awareness that all indicators are statistical rather than absolute, as implied by their single line displays. Shed light on several advanced cookbook filters. These include the SuperSmoother and Roofing Filters. Showcase new advanced indicators like the Even Better Sinewave and Decycler Indicators. Explain how to use transforms to improve the display and interpretation of indicators."--
Computing the Hilbert TransformerThe Hilbert Transformer Indicator; Using the Hilbert Transformer to Computethe Dominant Cycle; Dual Differentiator; Phase Accumulation; Homodyne; Key Points to Remember; Chapter 15 Indicator Transforms; Fisher Transform; Inverse Fisher Transform; Cube Transform; Key Points to Remember; Chapter 16 Swami Charts; SwamiCharts Overview; SwamiCharts RSI; SwamiCharts Stochastic; Roll Your Own SwamiCharts; Key Points to Remember; Chapter 17 Swing-Trading Strategies; Conventional Wisdom; Anticipating the Turning Point; Sine Wave Uniqueness; Safety Valve.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Technical analysis (Investment analysis); Investment analysis; Financial risk management; Investment analysis; Technical analysis (Investment analysis); BUSINESS & ECONOMICS -- Finance; Investment analysis; Technical analysis (Investment analysis); Electronic books